PENGARUH STRUKTUR KEPEMILIKAN, DEWAN KOMISARIS INDEPENDEN, DAN KOMITE AUDIT TERHADAP PENGUNGKAPAN MANAJEMEN RISIKO PADA PERUSAHAAN PERBANKKAN YANG TERDAFTAR DI BEI 2021-2023 - Pebrianti, Ferli; Setiorini, Hesti; Partama putra, Yudi; Khair, Ummul (Universitas Muhammadiyah Bengkulu, 2025)
This research aims to test and prove the influence of Ownership Structure, Independent Board of Commissioners, and Audit Committee on Risk Management Disclosure. The population in this study are banking companies listed on the Indonesia Stock Exchange for the 2021-2023 period, consisting of 47 companies. The number of samples in this research was 32 samples determined through purposive sampling. The method used is a quantitative method processed with SPSS 30. This research analyzes banking risk management disclosures based on the COSO Enterprise Risk Management (COSO ERM) framework. The techniques and data analysis used are descriptive statistics and multiple linear regression analysis.Based on the results of the research conducted, it shows that all variables simultaneously influence risk management disclosure in banking companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The partial research results show that the independent board of commissioners and audit committee variables have an effect on risk management disclosure, while management ownership and institutional ownership have no effect on risk management disclosure. Keyword: Independent Board Of Commissioners, Audit Committee, Risk Management Disclosure, Ownership Structure